2021
DOI: 10.24815/siele.v8i2.19214
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' beliefs and classroom practices on the use of video in English language teaching

Abstract: In the last decade, there has been a growing interest in exploring why teachers decide to and not to use a technological tool in their teaching practices. Teachers’ beliefs have appeared to be one of the influential factors, yet still little is known about what causes both consistencies and inconsistencies between teachers’ beliefs and their classroom practices, especially on the use of technology. Thus, to address such a gap, this study examined teachers’ beliefs about video and their use of video in English … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…The review also included an overview of Padlet, students' perspective of teacher's written feedback and its educational applications in English language teaching (ELT). Despite the empirical evidence reporting the positive outcomes of incorporating technology in ELT classrooms (Rofiah & Waluyo, 2020;Waluyo & Apridayani, 2021), some teachers in the study's context are still reluctant to use virtual interactive platforms e.g., Padlet in their EFL classrooms, citing the concerns of students' digital deficiency, lack of digital experience, contracted cheating and unsuitability of these mediated learning tools Besides, little is known about how low-proficiency students perceive the usefulness of Padlet-mediated feedback for their EFL writing development and how their perceptions correspond with their writing learning outcomes. Therefore, the present study intends to address these research gaps.…”
Section: Padlet and Its Pedagogical Usementioning
confidence: 99%
“…The review also included an overview of Padlet, students' perspective of teacher's written feedback and its educational applications in English language teaching (ELT). Despite the empirical evidence reporting the positive outcomes of incorporating technology in ELT classrooms (Rofiah & Waluyo, 2020;Waluyo & Apridayani, 2021), some teachers in the study's context are still reluctant to use virtual interactive platforms e.g., Padlet in their EFL classrooms, citing the concerns of students' digital deficiency, lack of digital experience, contracted cheating and unsuitability of these mediated learning tools Besides, little is known about how low-proficiency students perceive the usefulness of Padlet-mediated feedback for their EFL writing development and how their perceptions correspond with their writing learning outcomes. Therefore, the present study intends to address these research gaps.…”
Section: Padlet and Its Pedagogical Usementioning
confidence: 99%
“…Educ. (2023) 8:34 language instructors with new avenues to teach writing skills (Lund, 2008;Waluyo & Apridayani, 2021). Studies indicate that wikis enhance learning, improve writing abilities, and promote learner autonomy (Sun & Qiu, 2014;Wang, 2015;Wichadee, 2010).…”
Section: Process-genre Approach and Technologymentioning
confidence: 99%
“…Although previous studies have revealed numerous benefits of using video clip subtitles in learning English vocabulary, the use of two subtitles of English-Indonesian at once in one film, film clip, or video consisting of several parts is still not quite often created and utilized by the teachers in the sub-urban areas of EFL classroom context in Indonesia. For instance, Waluyo and Apridayani (2021) revealed that teachers' beliefs about the use of video in ELT were positive but inconsistent with their practices due to their teaching philosophy, knowledge and skill, facility, and reading of the literature. Moreover, it also applies to the Acehnese in the Indonesian context (i.e., Aceh is one of the provinces in Indonesia).…”
Section: Figure 1 An Illustration Of Five Parts Prototype Video Clip ...mentioning
confidence: 99%